Case Report: Strumal carcinoid tumor in the ovary: report of a rare occurrence with a review of literature - Zhu, Wei; Xu, Yuance; Yao, Qin (Frontiers in Medicine, 2025)
BackgroundPrimary ovarian carcinoid is a rare type of tumor that accounts for 0.5 to 1.7% of all carcinoid tumors and 1% of all ovarian cancers. These tumors can be classified into four types based on their histopathological features: island-like, trabecular, oral, and mucinous. Island-like carcinomas are more common in Western countries, while chain and trabecular carcinomas are more common in Asian countries. Ovarian strumal carcinoid, a specific type of ovarian tumor that often contains benign thyroid tissue, is a highly differentiated teratoma characterized by the co-existence of thyroid follicular and carcinoid tissues, along with neuroendocrine functions. Preoperative diagnosis is often challenging due to the occult nature and radiographic diversity of the tumor.Case reportThis case report details the diagnosis and treatment of pelvic masses in a 42-year-old patient. The patient had a 3-year clinical history. Ultrasound examination revealed an uneven echo mass measuring 5.1 × 4.0 × 4.3 cm in the right adnexal area with internal striped blood flow signals. However, the levels of CA-125, alpha-fetoprotein (AFP), free T4, thyroid stimulating hormone (TSH), and other diagnostic indicators were all within the normal range. The patient underwent laparoscopic resection of the right adnexa, and the histopathological findings confirmed the presence of an ovarian strumal carcinoid. The patient had a history of persistent constipation and, at the time of the study, reported right upper abdominal distension without dizziness, weakness, lower abdominal distension discomfort, and/or frequent urination. There had been no significant changes in her weight. At the 1-year postoperative follow-up, the patient showed no evidence of recurrence.DiscussionThrough a literature review, we discuss the clinical, imaging, and pathological features of this disease, as well as the outcome of surgical treatment. This report highlights the importance of careful evaluation and timely surgical intervention of pelvic masses. It also emphasizes that rare conditions such as ovarian strumal carcinoid should be taken into account when evaluating atypical ovarian tumors.